Role of L-lactate as an energy substrate in primary rat podocytes under physiological and glucose deprivation conditions - Maria Szrejder; Marlena Typiak; Piotr Pikul; Irena Audzeyenka; Patrycja Rachubik; Dorota Rogacka; Magdalena Narajczyk; Agnieszka Piwkowska (European Journal of Cell Biology, 2023)
Lactate has long been acknowledged to be a metabolic waste product, but it has more recently been found as a fuel energy source in mammalian cells. Podocytes are an important component of the glomerular filter, and their role in maintaining the structural integrity of this structure was established. These cells rely on a constant energy supply and reservoir. The utilization of alternative energy substrates to preserve energetic homeostasis is a subject of extensive research, and lactate appears to be one such candidate. Therefore, we investigated the role of lactate as an energy substrate and characterize the lactate transport system in cultured rat podocytes during sufficient and insufficient glucose supplies. The present study, for the first time, demonstrated the presence of lactate transporters in podocytes. Moreover, we observed modified the amount of these transporters in response to limited glucose availability and after l-lactate supplementation. Simultaneously, exposure to l-lactate preserved cell survival during insufficient glucose supply. Interestingly, during glucose deprivation, lactate exposure allowed the steady flow of glycolysis and prevented glycogen reserves depletion. Summarizing, podocytes utilize lactate as an energy substrate and possess a developed system that controls lactate homeostasis, suggesting that it plays an essential role in podocyte metabolism, especially during fluctuations of energy availability.